ChemInform Abstract: Quantum‐Chemical Characterization of the Properties and Reactivities of Metal‐Organic Frameworks. Issue 32 (August 2015) - Odoh, Samuel O.; Cramer, Christopher J.; Truhlar, Donald G.; Gagliardi, Laura
Abstract Review: 653 refs.